2020
DOI: 10.3390/en13051109
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Monitoring System for Predictive Maintenance of High Voltage Apparatus

Abstract: The online monitoring of a high voltage apparatus is a crucial aspect for a predictive maintenance program. Partial discharges (PDs) phenomena affect the insulation system of an electrical machine and—in the long term—can lead to a breakdown, with a consequent, significant economic loss; wind turbines provide an excellent example. Embedded solutions are therefore required to monitor the insulation status. The paper presents an online system that adopts unsupervised methodologies for assessing the condition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The lower part of Table 1 reports the references for the explicit empirical models [21,[26][27][28][29][30]. In [31], a fully unsupervised approach detected changes in the life status of a specimen. The authors showed that such an approach could be combined with the method proposed [29,30] to improve the insulation lifetime predictions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower part of Table 1 reports the references for the explicit empirical models [21,[26][27][28][29][30]. In [31], a fully unsupervised approach detected changes in the life status of a specimen. The authors showed that such an approach could be combined with the method proposed [29,30] to improve the insulation lifetime predictions.…”
Section: Related Workmentioning
confidence: 99%
“…Problems arise only in the very first part of the lifetime of the specimen. In fact, fast changes affect the insulation material when the PD inception occurs [30,31]. Hence, one may expect the model to be less accurate in that phase.…”
Section: Algorithm 2 Evaluation Inputmentioning
confidence: 99%
“…However, in cases where individual data profiles were closely similar, the method suffered from a lack of useful discharge features, impacting the accuracy of localized discharge pattern-recognition. The literature [32] developed an HV equipment monitoring system based on embedded technology, designed specifically to monitor the occurrence of PD phenomena in the insulation layer. Nevertheless, it could not accurately classify specific discharge types using deep-learning techniques.…”
Section: Introductionmentioning
confidence: 99%